PENGETAHUAN PASANGAN USIA SUBUR (ISTRI) TENTANG ALAT KONTRASEPSI PIL DI DESA SIGUMPAR KECAMATAN SIGUMPAR KABUPATEN TOBA - Erita Saragih (STIKes Murni Teguh, 2020)
The pill has a high effectiveness with a success rate of 99% and a failure rate that occurs around 2-8%. If taken according to the rules the failure will be 0.1%. The hormones contained in each pill are a very good blend of ingredients, so the hormone content and composition of substances in each pill are the same. This type of research is descriptive. This study aims to gain knowledge of the Fertile Age Couple (wife) about contraceptive pill in the village of Sigumpar, Sigumpar District, Kabuaten Toba. This research was conducted using interviews and questionnaires, to select samples using random sampling (random) of 58 Fertile Age Couples (wife), using primary data and secondary data by distributing questionnaires as many as 30 questions to Fertile Age Couples (wife). From this study the number of Pus (wives) of knowledge was obtained as many as 19 respondents (32.76%). Based on age, the majority of Pus (wives) with sufficient knowledge are 7 respondents (12.06%) at the age level of 31-34 years, based on education the majority of Pus (wives) have enough knowledge of 10 respondents (17.25%) in secondary education, based on the majority of Pus (wife) knowledgeable jobs are 14 respondents (24.13%) in the group that does not work, based on information sources the majority of Pus (wife) knowledgeable are 17 respondents (29.31%) who get information sources. Based on the research above shows that the level of knowledge of Pus (wife) is sufficiently categorized. It is expected that health workers provide more information and counseling about the Pill for and to couples of childbearing age (wives) in order to use birth control pills regularly to prevent pregnancy. Abstrak Pil mempunyai efektivitas yang tinggi dengan tingkat keberhasilan 99% dan angka kegagalan yang timbul sekitar 2-8%. Jika diminum sesuai aturan maka kegagalannya menjadi 0,1%. Hormon yang terkandung pada setiap pil merupakan perpaduan bahan yang sangat baik, sehingga kandungan hormon dan komposisi zat di setiap pil sama. Jenis penelitian ini adalah deskriptip. Penelitian ini bertujuan untuk mendapatkan pengetahuan Pasangan Usia Subur (istri) tentang alat kontrasepsi pil di Desa Sigumpar Kecamatan Sigumpar Kabuaten Toba. Penelitian ini dilakukan dengan menggunakan wawancara dan kuesioner, untuk memilih sampel menggunakan random sampling (acak) sebanyak 58 Pasangan Usia Subur (istri), menggunakan data primer dan data sekunder dengan membagikan kuesioner sebanyak 30 soal kepada Pasangan Usia Subur (istri). Dari penelitian ini di peroleh jumlah Pus (istri) pengetahua cukup sebanyak 19 responden (32,76%). Berdasarkan umur, Mayoritas Pus(istri) berpengetahuan cukup sebanyak 7 responden (12,06%) pada tingkatan umur 31-34 tahun, berdasarkan pendidikan mayoritas Pus (istri) berpengetahuan cukup sebanyak 10 responden (17,25%) pada pendidikan menengah, berdasarkan pekerjaan mayoritas Pus (istri) berpengetahuan cukup sebanyak 14 responden (24,13%) pada kelompok yang tidak bekerja, berdasarkan sumber informasi mayoritas Pus (istri) berpengetahuan cukup sebanyak 17 responden (29,31%) yang mendapatkan sumber informasi. Berdasarkan penelitian di atas menunjukan bahwa tingkat pengetahuan Pus(istri) di ketegorikan cukup. Di harapkan kepada petugas kesehatan agar lebih memberikan informasi dan penyuluhan tentang Alat Kontrasepsi Pil kepada dan kepada Pasangan usia subur (istri) agar dapat menggunakan Pil KB secara teratur untuk mencegah kehamilan.